'And so to Pepys' – the other side of the knife. Issue 2 (15th March 2022) - Goddard, Jonathan Charles
Abstract : Surgery without anaesthetic would be unthinkable these days, but when Samuel Pepys had a bladder stone removed in 1658 it was the norm. Here the author shares some fascinating insights into the life of England's famous diarist and the experience of 17th century surgery.